The Influence of Perception and Religiosity on Consumer Behaviour: A Perspective of Consumption in Al-Qur'an - Devid Frastiawan Amir Sup; Mohamad Zaenal Arifin; Ziad Abdurrahman Azzahid; Ulfatun Wahidatun Nisa (Al-Amwal : Jurnal Ekonomi dan Perbankan Syari'ah, 2026)
Introduction: This research aims to identify the influence of perception and religiosity on consumer behaviour at Otsmani Coffee Solo, and to identify whether perception and religiosity have a significant influence on consumer behaviour patterns at Otsmani Coffee.Methods: This research used a quantitative, survey-based approach. This study used Partial Least Squares (PLS) with SmartPLS version 4.1.9.4 as the analysis tool.Results: This research found that customer perceptions and religiosity significantly influence consumer behaviour when purchasing at Otsmani Coffee Solo. This research confirmed that attitudes, subjective norms, and behavioral control influence customers' intentions and purchase decisions. In addition, Otsmani Coffee Solo's market competitiveness was influenced by factors such as product suitability, brand identity, customer loyalty, emotional attachment, and differentiation from competitors.Conclusion and suggestion: The results suggest that value-based and identity-based marketing strategies that match consumer preferences and beliefs are essential for consistently increasing customer attraction and loyalty. Furthermore, consumers need to adhere to the concept of consumption in the Quran: consuming what is halal and tayyib; being proportionate, not excessive (israf), and not stingy (bakhil); and always acknowledging the blessings of Allah SWT.